1996
DOI: 10.1016/0735-1097(95)00526-9
|View full text |Cite
|
Sign up to set email alerts
|

Aortic atherosclerotic plaques as a source of systemic embolism

Abstract: Complicated atherosclerotic plaques in the aortic arch represent an independent risk factor for systemic embolism similar to atrial fibrillation and severe atherosclerosis of the carotid arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 42 publications
2
80
1
Order By: Relevance
“…The presence of thrombi on aortic plaques was further documented on autopsy in a more recent study, 46 which found aortic thrombi in 17 of 120 cases, as well as a significant association of complex plaque with previous emboli. In addition, mobile lesions in the aorta seen on TEE in 6 patients were seen to be thrombi on surgical pathology.…”
Section: Pathological Correlationsmentioning
confidence: 99%
“…The presence of thrombi on aortic plaques was further documented on autopsy in a more recent study, 46 which found aortic thrombi in 17 of 120 cases, as well as a significant association of complex plaque with previous emboli. In addition, mobile lesions in the aorta seen on TEE in 6 patients were seen to be thrombi on surgical pathology.…”
Section: Pathological Correlationsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Aortic atheroma is recognized as an important marker of stroke and peripheral embolism in patients with AF. [7][8][9] The SPAF-III investigators reported that complex aortic plaque emerged as a risk factor of thromboembolism in patients with nonrheumatic AF, and warfarin was effective in reducing stroke in patients with AF and complex aortic plaque. 10 Complex aortic plaques with ulcerated or mobile plaques and superimposed thrombi would activate hemostatic markers.…”
mentioning
confidence: 99%
“…Because cardioembolism in our series and in others is the main cause of systemic embolization, 2,11,19 the discovery of SDVI associated with cryptogenic stroke should be taken into account in the diagnosis of probable cardiac embolism and therefore may assist in making decisions for anticoagulant therapy. Earlier studies 20,21 described the association between complex atherosclerotic plaques in the thoracic aorta and peripheral embolic events. We did not find any association between SDVI and ulcerated plaques in the abdominal or thoracic aorta among patients with brain infarction, but we could not exclude that this association was overlooked as a result of the lack of statistical power.…”
Section: Discussionmentioning
confidence: 99%